Dietary intake of sulforaphane-rich broccoli sprouts decreases fecal calprotectin levels in patients with ulcerative colitis - Yanaka, Akinori; Ohmori, Toshihide; Ochi, Masanori; Suzuki, Hideo (Functional foods in health and disease, 2024)
Background: Ulcerative colitis (UC), which is linked to chronic oxidative stress, has been on the rise in Japan, attributed to the recent Westernization of dietary habits.  Sulforaphane, which is abundant in broccoli sprouts (BS), has been shown to enhance antioxidant activity by up-regulating nrf2-mediated antioxidant enzymes. We have previously shown that the dietary intake of sulforaphane-rich broccoli sprouts mitigates H.pylori-induced gastritis not only by enhancing nrf2-dependent anti-oxidant activity against oxidative stress from H.pylori infection, but also by directly inhibiting H.pylori activity (Cancer Prev Res 2:353-360,2009). In this study, we examined if the dietary approach with BS affects intestinal microbiota, thereby mitigating colonic inflammation in mesalazine-treated human UC patients. Objective: In this study, we examined if dietary intake of sulforaphane-rich broccoli sprouts decreases fecal calprotectin levels in patients with ulcerative colitis Methods: This study was registered with the University hospital Medical Information Network (UMIN) in Japan under the Clinical Trial Registration Number, UMIN000041972. Twenty-eight mild UC patients treated with mesalazine were divided between the sulforaphane-rich BS group (n=14) or the sulforaphane-free alfalfa sprouts (AS) group (n=14). These subjects were instructed to take 20 g of raw BS or AS daily for 8 weeks, with BS containing 4.4 mg/g glucoraphanin, a precursor of sulforaphane, and AS containing no glucoraphanin. Stool samples were obtained just before and after the 8 weeks sprouts treatment. Levels of fecal calprotectin were measured as the quantitative indices for colonic mucosal inflammation. We conducted an examination of gut bacteria through a method called terminal restriction fragment length polymorphism (TR-FLP) analysis of fecal samples. Results: 1. Twelve patients from the BS group and 11 from the AS group completed the intervention study as requested. 2. Only the treatment with BS caused a significant decrease in the level of fecal calprotectin as well as an increase in the fecal component of Clostridium subcluster IV and XIVa, which have been reported to enhance butyrate production. 3. There was no change in the clinical activity index after intake of either the BS or the AS. Conclusion: These results indicate that dietary approach with sulforaphane-rich BS mitigates colonic inflammation in mesalazine-treated UC patients. Our data also suggest that the beneficial effects of the BS may be related with the increase in butyrate-producing intestinal microbiota by dietary approach with sulforaphane.